Correlation between the expression of folate receptor alpha (FRα) and clinicopathological features in patients with lung adenocarcinoma. (July 2020) - Tamura, Nobumasa; Fujiwara, Yutaka; Hashimoto, Taiki; Shiraishi, Hideaki; Kitano, Shigehisa; Shimizu, Toshio; Kuwano, Kazuyoshi; Yamamoto, Noboru; Motoi, Noriko
Highlights: We evaluated the tumor FRα expression in tissue microarrays of lung adenocarcinoma. FRα expression was higher in EGFR -mutated adenocarcinoma than in EGFR wild type. The high FRα expression was related to low PD-L1 expression and a few CD8+ cells. The high FRα expression was related to widely spread cancer-associated fibroblasts. We suggest that FRα may become a target for the treatment of lung adenocarcinoma. Abstract: Objectives: Folate receptor alpha (FRα) is expressed on the cell surface, mediates its intracellular transport via receptor-mediated endocytosis, and is involved in cell division. Whether FRα could be a potential therapeutic target in FRα-expressing cancers remains unknown. Here, we retrospectively investigated the correlations between tumor FRα expression in lung adenocarcinoma (LADC) and clinicopathological features. Materials and methods: FRα expression was evaluated using a tissue microarray (TMA) constructed from surgical specimens of LADC and compared with clinicopathological features including the EGFR mutation status and the expressions of PD-L1, PD-L2, PD-1, CD4, CD8, CD204, and αSMA. If the proportion of positively stained tumor cells was greater than or equal to 5%, the tumor was considered to show FRα expression; if the H-score was more than or equal to 60, the tumor was considered to show high FRα expression. Results: Overall, 466 TMA cores created from 233 LADC patients were evaluated: FRα-positive expression (FRα-pos)/negative (FRα-neg), 222/11; FRα high expression (FRα-HE)/low (FRα-LE), 190/43. An EGFR mutation was present in 53.2 % of the patients. The median H-score of FRα expression, FRα-pos rate, and FRα-HE rate for EGFR mutation/wild type were 159/104 ( p  = 0.0002), 97.6/92.7 % ( p  = 0.0773), and 88.7/73.4 % ( p  = 0.0026), respectively. The H-scores for FRα had mild correlations with the proportion of tumor cells with positive staining for PD-L1 ( r =-0.2557, p  < 0.0001), the number of CD8-positive cells per square millimeter ( r =-0.1767, p  = 0.0069), and the area with positive staining for αSMA ( r  = 0.2049, p  = 0.0017). No correlations were seen between FRα expression and other cancer-immunity markers. Conclusion: Tumor FRα expression was significantly higher in LADCs with EGFR mutation than in those with wild-type EGFR . This study suggested that FRα expression was related to cancer and microenvironment-immunity markers such as PD-L1 expression, CD8 cells, and αSMA.